Pengembangan Model Pembelajaran Berbasis pendidikan Lingkungan dengan Lahan Basah pada MI di Kota Banjarmasin - Khairunnisa Khairunnisa; Salamah Salamah (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2017)
Human being and environment are depending on each other. The carrying capacity of the environment requires human being to care for and preserve the environment for the sake of sustainability. . Effort and love for environment have to be taught to children since childhood at school in a form of environmental education. What is meant by environment here is the dominant environment at South Kalimantan; and that is wetland, such as river. There has to be an effort to introduce wetland to students in a form of learning model in order to grow their caring and loving attitudes for the environment. This research is aimed to know how the environmental based learning by introducing wetland at Islamic elementary schools in Banjarmasin have been going recently (teachers’ understanding, design, process, and learning evaluation), and how are the learning model which is based on environmental education on wetland can be developed and implemented at Islamic elementary schools in Banjarmasin. This research is a developmental research with Research and Development (R&D) approach through preliminary research, small scale testing model development, and wide scale testing model validation. The research is conducted at MI Darun Nasihin, MI Sulamut Taufiq, and MI Nurul Islam. The data is collected through documentation, questionnaires, interview, and observation. The data is analyzed descriptive-qualitatively through data reduction, data display, and verification. After wide scale testing on the model which was developed and tried out using learning instrument adapted with the materials about ecosystem balance, the materials were then taught to the six graders of Islamic elementary school through the following implementation steps: orientation, relating, exploration, finding problems, group investigation, work result discussion, clarification, and resolution. The model is proved to be able to be developed at Islamic elementary schools in Banjarmasin, viewed from the students learning evaluation with the percentage in very good category. Students behavior also shows positive influence which means the learning has been able to stimulate students’ positive behaviors such as caring, being open-minded, being appreciative to what people are saying, and being responsible. The model development is also supported by good response from students and teachers towards students’ workbook and teaching learning process.